Case report: An N-of-1 study using amplitude modulated transcranial alternating current stimulation between Broca's area and the right homotopic area to improve post-stroke aphasia with increased inter-regional synchrony - Omae, Erika; Shima, Atsushi; Tanaka, Kazuki; Yamada, Masako; Cao, Yedi; Nakamura, Tomoyuki; Hoshiai, Hajime; Chiba, Yumi; Irisawa, Hiroshi; Mizushima, Takashi; Mima, Tatsuya; Koganemaru, Satoko (Frontiers in Human Neuroscience, 2024)
Over one-third of stroke survivors develop aphasia, and language dysfunction persists for the remainder of their lives. Brain language network changes in patients with aphasia. Recently, it has been reported that phase synchrony within a low beta-band (14-19 Hz) frequency between Broca's area and the homotopic region of the right hemisphere is positively correlated with language function in patients with subacute post-stroke aphasia, suggesting that synchrony is important for language recovery. Here, we employed amplitude-modulated transcranial alternating current stimulation (AM-tACS) to enhance synchrony within the low beta band frequency between Broca's area and the right homotopic area, and to improve language function in a case of chronic post-stroke aphasia. According to an N-of-1 study design, the patient underwent short-term intervention with a one-time intervention of 15 Hz-AM-tACS with Broca's and the right homotopic areas (real condition), sham stimulation (sham condition), and 15 Hz-AM-tACS with Broca's and the left parietal areas (control condition) and long-term intervention with sham and real conditions (10 sessions in total, each). In the short-term intervention, the reaction time and accuracy rate of the naming task improved after real condition, not after sham and control conditions. The synchrony between the stimulated areas evaluated by coherence largely increased after the real condition. In the long-term intervention, naming ability, verbal fluency and overall language function improved, with the increase in the synchrony, and those improvements were sustained for more than a month after real condition. This suggests that AM-tACS on Broca's area and the right homotopic areas may be a promising therapeutic approach for patients with poststroke aphasia.